Multicultural Islamic Religious Education Based on Local Wisdom: The Analysis of "SILAS" Values in Sundanese Culture - Dewi Anggraeni; Andy Hadiyanto; Ahmad Hakam (Indonesian Journal of Islamic Education Studies (IJIES), 2023)
Extreme religious understanding is one of the potentials that can hinder a harmonious religious life. Islamic religious education at universities has a significant role in shaping moderate attitudes. Multicultural Islamic Religious Education based on local wisdom aims to integrate the concept of multiculturalism by adopting local wisdom SILAS. This qualitative analytical research was conducted by analyzing the values silih asah, silih asih, and silih asuh (SILAS) as one of the local wisdom of the Sundanese culture. From data collection through observation, interviews, and documentation studies then analyzed, it is known that SILAS, as a Sundanese cultural philosophy contains harmonious values in building human qualities that can be integrated into Islamic Religious Education learning. The results of this study show that the essence of SILAS is universal to human values in line with religious values. The multicultural approach based on local wisdom in Sundanese culture SILAS is inseparable from educational aspects, such as ontological relationship with God, epistemology, openness to knowledge, and axiology to uphold human values. Islamic Religious Education learning with local culture provides competence to students to analyze and provide ideas or solutions to various cultural and religious conflicts.